2020
DOI: 10.11646/zootaxa.4821.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Description and ecology of a new species of the cricket genus Endecous (Orthoptera: Grylloidea: Phalangopsidae) in the speleological province of Arcos-Pains-Doresópolis, Southeastern Brazil

Abstract: A new cricket species of the genus Endecous Saussure, 1878 is described in the present work found in the speleological province of Arcos-Pains-Doresópolis, which belongs to the limestone group Bambuí, Brazil. Moreover, the spatial distribution of the new species was related to the species Eidmanacris sp., which co-occurs with the former in several caves. Relationships between species abundance and horizontal projection, number of entrances and environmental stability of the caves where these species coexist we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 464 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Analysis in different temporal scenarios (21 ka, 6 ka, 0 ka and RCP8.5) based on the current Endecous distribution showed that these crickets almost did not reach the north of the Amazon biome. The same pattern was observed for the sympatric genus Eidmanacris Chopard, 1956(Castro-Souza et al 2020b, a group that is also dependent on remnants of humid forests and cave habitats (De Campos et al 2021). Although these two genera can co-occur inside caves, there is spatial segregation between their populations, with Endecous inhabiting deeper regions and Eidmanacris occurring near cave entrances, which would avoid competitive exclusion (Castro-Souza et al 2020b, Paixão et al 2017.…”
Section: The Atlantic Rainforests As a Source And Temporal Refuge Of ...mentioning
confidence: 75%
See 2 more Smart Citations
“…Analysis in different temporal scenarios (21 ka, 6 ka, 0 ka and RCP8.5) based on the current Endecous distribution showed that these crickets almost did not reach the north of the Amazon biome. The same pattern was observed for the sympatric genus Eidmanacris Chopard, 1956(Castro-Souza et al 2020b, a group that is also dependent on remnants of humid forests and cave habitats (De Campos et al 2021). Although these two genera can co-occur inside caves, there is spatial segregation between their populations, with Endecous inhabiting deeper regions and Eidmanacris occurring near cave entrances, which would avoid competitive exclusion (Castro-Souza et al 2020b, Paixão et al 2017.…”
Section: The Atlantic Rainforests As a Source And Temporal Refuge Of ...mentioning
confidence: 75%
“…In particular, many South American cave phalangopsidae (e.g. Adelosgryllus, Endecous, Phalangopsis and Strinatia) (Campos et al 2017, Castro-Souza et al 2020b, Cigliano et al 2022, Junta et al 2020, Merlo et al 2022, Mesa et al 1999) reveal pre-adaptations reported for other cave crickets (Desutter-Grandcolas 1993;Desutter-Grandcolas 1997;Heads 2010), such as eye size reduced, loss of ocelli, absence of auditory tympana and body discoloration. However, to confirm that the traits are pre-adaptations, it is necessary to evaluate them together with the habitat from a phylogenetic perspective (Desutter-Grandcolas 1997).…”
Section: Caves As Potential Refuges For the Species Conservation In T...mentioning
confidence: 96%
See 1 more Smart Citation